The effectiveness of the papaya seed (Carica papaya L) for reproductive function of Tilapia, Oreochromis niloticus (Linnaeus, 1758) - Munawar Khalil; Yunidar Yunidar; Mahdaliana Mahdaliana; Munawwar Khalil; Rachmawati Rusydi; Zulfikar Zulfikar (Jurnal Iktiologi Indonesia, 2019)
Introduction fish in Indonesia has been negatively impact to the water ecology, such as declining in the number of native fish species. Handling the negative impacts of introduced fish can be minimized by reducing fertility rates through the use of plant compound extracts. This study was conducted in May - June 2016 which aimed to assess the effectiveness of the papaya seed flour (Carica papaya L) for the reproductive function of introduction fish Oreochromis niloticus. The research design used in this study was completely randomized design, non-factorial with five treatments and three replications, namely A: control (without giving the flour), B: 40 mg, C: 50 mg, D: 60 mg, E: 70 mg of papaya seeds flour mixing in 100 grams of artificial feed. The fish sample used were 45 mature tilapia fish, 4-5 months old with 200 g in weight for female and 250 gram in weight for male. Parameters measured in this research were feed consumption level, fecundity, fertilization rate, hatching rate and sperm morphological structures. The results of this study indicated that the papaya seed flour gave the multiple effect on the sperm abnormality and decreased the motility level of sperm. Statistical analysis showed that the application of papaya seed flour gave significantly different effect (P <0.05) between treatments on percentage of fertilization level and hatching rate parameters, but showed not significantly different on survival rate parameter where P> 0.05. The lowest sperm motility rate was found in treatment E, which was 00.45 ".032 /second. The average eggs number in this study ranged from 994,33 to 1.416 grains, whereas the lowest fertilization level and the lowest hatching rate was in treatment E with the percentage 58.58% and 99.24%. Abstrak Ikan introduksi di Indonesia telah menimbulkan beberapa dampak negatif terhadap ekologi perairan, diantaranya adalah menurunnya spesies ikan asli. Penanganan dampak negatif ikan-ikan introduksi dapat diminimalkan dengan cara menurunkan angka fertilitas melalui penggunaan ekstrak senyawa tumbuhan. Penelitian ini dilaksanakan pada bulan Mei – Juni 2016 yang bertujuan untuk menganalisis efektivitas tepung biji pepaya (Carica papaya L) dalam menurunkan fungsi reproduksi ikan nila Oreochromis niloticus. Rancangan penelitian yang digunakan adalah rancangan acak lengkap non-faktorial dengan lima perlakuan tiga ulangan yaitu A: Kontrol (tanpa pemberian tepung), B: Pemberian 40 mg, C: 50 mg, D: 60 mg, E: 70 mg tepung biji pepaya dalam 100 g pakan buatan. Ikan sampel yang digunakan adalah induk ikan nila sebanyak 45 ekor yang berumur 4-5 bulan dengan berat bobot tubuh 200 g untuk induk betina dan 250 g untuk induk jantan. Parameter yang diukur ialah daya konsumsi pakan, jumlah telur (fekunditas), tingkat pembuahan telur, tingkat penetasan telur, dan morfologi sperma. Hasil penelitian menunjukkan bahwa tepung biji pepaya memberikan efek terhadap abnormalitas sperma dan menurunkan sintasan sperma, dan penurunan tingkat pembuahan telur (fertilitas rendah). Analisis statistik menunjukkan bahwa pemberian tepung biji pepaya memberikan pengaruh yang berbeda nyata (P<0,05) antar perlakuan pada parameter persentase pembuahan dan penetasan telur, namun tidak berbeda nyata terhadap parameter sintasan (P>0,05). Angka motilitas sperma terendah dijumpai pada perlakuan E yaitu 00.45”.032/detik. Jumlah telur pada penelitian ini berkisar rata-rata 994,33-1416 butir dengan nilai pembuahan terendah dan penetasan terendah terdapat pada perlakuan E dengan persentase 58,58% dan 99,24%.